Fertility outcomes after laparoscopic partial bladder resection for deep endometriosis: Retrospective analysis from two expert centres and review of the literature. (January 2018) - Nyangoh Timoh, Krystel; Ballester, Marcos; Bendifallah, Sofiane; Fauconnier, Arnaud; Darai, Emile
Abstract: Objective: To evaluate fertility outcomes after laparoscopic partial bladder resection in women with bladder endometriosis and to review the literature. Study design: A retrospective study conducted at two tertiary referral centres –Tenon University Hospital and Poissy University Hospital (Canadian Task Force Classification Level II-2)–from July 2006 to November 2015. Patients with bladder endometriosis who underwent either laparoscopic partial bladder resection (PBR) alone for those without posterior endometriotic lesions (PBR group) or both laparoscopic PBR and associated posterior deep infiltrating endometriosis (DIE) resection (PBR-PDIE group) were included. Pregnancy and live birth rates according to prior infertility, and associated posterior DIE resection were analysed. Results: Thirty-four patients were included; 15 in the PBR group and 19 in the PBR-PDIE group. The median age (range) was 31 years (25–37), Seventeen patients (50%) had prior infertility. The median follow-up after bladder resection was 60.6 months (12–116). Overall, of the 25 (73.5%) patients who wished to conceive, 17 (68%) achieved pregnancies resulting in a live birth rate of 76.4%. Among the 17 patients with prior infertility, nine (52.9%) conceived. Overall, eight patients (53.3%) in the PBR group conceived and nine (47.3%) in the PBR-PDIE group (difference not significant). Conclusion: The present study demonstrates that laparoscopic PBR results in a high pregnancy rate in patients with prior infertility as well as in those with associated posterior DIE suggesting that surgery could be an acceptable alternative to first-line assisted reproductive technology.